2017
DOI: 10.1177/0160017617713822
|View full text |Cite
|
Sign up to set email alerts
|

Impact Evaluation of Investments in the Appalachian Region

Abstract: We evaluate the impact of a half century of nontransportation Appalachian Regional Commission (ARC) investments on its constituent counties using quasi-experimental methods. We apply a set of propensity score methods and select the most appropriate matching algorithm for use in identifying the effects of policy implementation. The results of the analyses indicate that counties that received ARC funding grew faster than the control counties. The long-run per capita income growth rate in ARC investment counties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…One notable example is the Appalachian Regional Commission (ARC), a regional economic development agency that coordinates federal and local economic resources to support distressed communities at the Appalachian region. 3 Evidence has shown that the ARC model is quite successful in improving rural economic outcomes (Isserman & Rephann, 1995; Sayago-Gomez et al, 2018). However, decreasing federal funding for rural development has imposed great challenges to those regional agencies (SSIT, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One notable example is the Appalachian Regional Commission (ARC), a regional economic development agency that coordinates federal and local economic resources to support distressed communities at the Appalachian region. 3 Evidence has shown that the ARC model is quite successful in improving rural economic outcomes (Isserman & Rephann, 1995; Sayago-Gomez et al, 2018). However, decreasing federal funding for rural development has imposed great challenges to those regional agencies (SSIT, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This result is consistent with the conclusions of Glaeser and Gottlieb (2008) on these types of economies. However, Rephann and Isserman (1994) came to the opposite conclusion in their assessment of Appalachian Regional Commission (ARC) transportation investment, and Sayago-Gomez, Piras, Jackson, and Lacombe (2017) more recently found small, but positive impacts from 50 years of ARC place-based nonhighway investments. Kline and Moretti (2014) studied the place-based Tennessee Valley Authority project and found positive direct impact on the region with long-lasting benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Appalachia is, and has been, a systematically lagging region associated with lower levels of labor force participation and higher levels of unemployment (Dorsey, 1991;Isserman and Rephann, 1993;Stephens and Deskins, 2018). For instance, this is the only region in the US with a dedicated policy-making commission, the Appalachian Regional Commission, which has been in place for over 50 years (Isserman and Rephann, 1993;Sayago-Gomez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%